2009
DOI: 10.1007/s10815-009-9295-9
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose affecting successful transplantation of vitrified-thawed mouse ovarian tissues

Abstract: Purpose The aim of this experiment is to detect effects of varying levels of sucrose on vitrified ovarian tissues. Methods Ovarian tissues of mice were vitrified-thawed. Mice were randomly assigned to the fresh control group and experimental groups. According to different concentration of sucrose in vitrification solution, the experimental groups were randomly divided into Group I (0.2 M sucrose), Group II (0.4 M sucrose), Group III (0.8 M sucrose) and Group IV (1.6 M sucrose). Cytology was followed throughout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
1
11
0
1
Order By: Relevance
“…We found a superior response in heterotopic implants compared with orthotopic implants, including the observation that the heterotopic cryopreserved implants lost fewer follicles in comparison to orthotopic implants. Our findings are consistent with those of other reports [ 1 ] and suggest that fresh and subcutaneous transplants exhibit a potential that has thus far not been effectively utilized in research [ 8 , 27 , 28 ].…”
Section: Resultssupporting
confidence: 93%
“…We found a superior response in heterotopic implants compared with orthotopic implants, including the observation that the heterotopic cryopreserved implants lost fewer follicles in comparison to orthotopic implants. Our findings are consistent with those of other reports [ 1 ] and suggest that fresh and subcutaneous transplants exhibit a potential that has thus far not been effectively utilized in research [ 8 , 27 , 28 ].…”
Section: Resultssupporting
confidence: 93%
“…A clear understanding of the events that occur during the early stages of ovarian tissue transplantation will therefore reduce injury to both the follicles and stromal cells. Previous studies have tracked the successful xenotransplantation of ovarian tissue into severe‐combined immunodeficiency disease (SCID) mice (Zhang et al, ; Amorim et al, ; Dittrich et al, ; Jafarabadi et al, ); here, we grafted thawed ovarian tissue onto a chick embryo chorioallantoic membrane (CAM) model for a short time to track the early events following transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…sucrose, enhances cell dehydration before freezing of extracellular water. It has been stated that sucrose concentrations ranging from 0.4 to 0.8 m are appropriate to vitrify mouse ovaries (Zhang et al. 2009).…”
Section: Introductionmentioning
confidence: 99%
“…sucrose, enhances cell dehydration before freezing of extracellular water. It has been stated that sucrose concentrations ranging from 0.4 to 0.8 M are appropriate to vitrify mouse ovaries (Zhang et al 2009). In a previous study, we have shown the suitability of 0.5 M sucrose in the vitrification of caprine ovarian tissue (Santos et al 2007a).…”
Section: Introductionmentioning
confidence: 99%